Possibilidade de discussão de cumulação de pedidos nas ações de embargos de terceiro: uma análise acerca dos limites cognitivos do juiz no curso da mencionada ação - SOUZA, Melissa Paola Pereira de (2024)
The present study aims to analyze the possibility of discussing cumulation of requests within the Third Party Embargo Action. To this end, we initially sought to carry out an analysis of the judge's cognitive act and the various aspects of this cognition, reporting that it can be summary or exhaustive, as well as that it can be examined from the aspects of the vertical and horizontal. Furthermore, the research sought to clarify, in an objective manner, all the nuances relating to the Third Party Embargo Action, demonstrating the main problems involving the aforementioned action to try to answer whether there is the possibility of discussing, in addition to the undue constriction, other requests that may may be in the initial. Finally, there was a jurisprudential analysis with the aim of verifying whether the jurisprudence corresponds with the bibliographic understanding on the subject, and it was found that those judged defend the restrictive nature of the Third Party Embargo Action, which, therefore, limits the judge's cognitive act .